MENINGKATKAN PRESTASI BELAJAR MEMBACA AL QURAN MELALUI MODEL PEMBELAJARAN TUTOR SEBAYA DI KELAS VII B SMP NEGERI 1 BATURETNO KABUPATEN WONOGIRI - Siti Safuroh (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
As the results of the initial test for reading the Al-Quran, learning achievement to read the Al-Quran in class VII B SMP Negeri 1 Baturetno is still low with an average score of 62.30. While the learning completion score has only reached 22%. In general, the learning process is still dominated by teachers. This research aimed to improve learning achievement in reading the Al Quran through optimizing learning activities. This research consists of three cycles, each cycle including the following steps: 1) Planning: creating a learning scenario using a peer tutor model, 2) Acting: carrying out learning according to the scenario, 3) Observing: taking data through triangulation as data validation, 4) Reflecting: the observation data is reflected collaboratively to determine improvements in achievement and plan further action. The results of this research show that there is a quite large increase in learning achievement in reading the Al Quran as follows: in cycle I there was an increase in the average score of 4.30 points (from 62.30 to 66.60) and an increase in learning completeness of 15% (from 22% to 37 %), in cycle II there was an increase in the average score of 8.20 points (from 66.60 to 74.80) and an increase in learning completeness of 29% (from 37% to 66%), and in cycle III there was an increase in the average score of 1.80 points (from 74.80 to 76.60) with an increase in learning completeness of 25% (from 66% to 91%). The same actions from cycle I to cycle III show an increase in student achievement in learning to read the Quran.